2021
DOI: 10.6061/clinics/2021/e2683
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol prevented intestinal ischemia and reperfusion-induced changes in intestinal permeability and motility in male rats

Abstract: OBJECTIVES: Ischemia and reperfusion (I/R) in the intestine could lead to severe endothelial injury, compromising intestinal motility. Reportedly, estradiol can control local and systemic inflammation induced by I/R injury. Thus, we investigated the effects of estradiol treatment on local repercussions in an intestinal I/R model. METHODS: Rats were subjected to ischemia via the occlusion of the superior mesenteric artery (45 min) followed by reperfusion (2h). Thirty min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Although the physical loss of the epithelial barrier appears short-lived, it is likely that altered permeability and bacterial translocation may persist until the near-complete restoration of the mucosa and its intercellular mucus stores. Previous studies indicated that bacterial translocation depended on multiple factors, including the extent of injury, bacterial strains in the intestine, and motility [26][27][28]. This is in line with our previous findings in the same animal model when lipopolysaccharide reached the highest circulating levels after 24 h of reperfusion [29] and suggests that increased permeability for bacteria and bacterial products may persist, despite the apparent morphological recovery.…”
Section: Discussionsupporting
confidence: 91%
“…Although the physical loss of the epithelial barrier appears short-lived, it is likely that altered permeability and bacterial translocation may persist until the near-complete restoration of the mucosa and its intercellular mucus stores. Previous studies indicated that bacterial translocation depended on multiple factors, including the extent of injury, bacterial strains in the intestine, and motility [26][27][28]. This is in line with our previous findings in the same animal model when lipopolysaccharide reached the highest circulating levels after 24 h of reperfusion [29] and suggests that increased permeability for bacteria and bacterial products may persist, despite the apparent morphological recovery.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, SI morphological damage and villus recovery were comparable with several previous results published by our group and others. 1519,40 In the present study, we observed the greatest damage at 30–60 min post-reperfusion in both the BK-IIRI and OSMA groups, with denuded villi and loss of villi (scores 4 and 5, respectively, on the Park/Chiu score) as the main characteristic lesions. The kinetic study facilitated the recovery of the intestinal mucosa, with edema (Park/Chiu score 1–2) as the predominant lesion at 24 h post-reperfusion and slight intestinal damage at 1 week after IIRI (Figure 5c).…”
Section: Discussionsupporting
confidence: 58%
“…For example, in the SI, superior mesenteric artery clamping model is currently used to evaluate IIRI, requiring one animal for each sample and study time. 1529 The same situation occurs in the field of experimental colitis, where old and recent scientific articles use one animal in each LI sample collection. 3037 For the reasons mentioned above, it is a challenge to develop models that enable reducing the number of animals involved in these studies.…”
Section: Introductionmentioning
confidence: 87%
“…Hence, intestinal barrier dysfunction caused by intestinal injury and consequently intestinal-derived infection via the mesenteric lymphatic pathway has become an important mechanism of organ damage. Studies have shown that E2 treatment could play beneficial roles in reducing intestinal permeability and inflammatory response after hemorrhagic shock or intestinal ischemia-reperfusion (37–40). The current results also showed E2 intervention significantly inhibited hemorrhagic shock–induced intestinal ischemia and intestinal villi irregularity, edema, and truncation, suggesting that E2 treatment alleviated intestinal injury.…”
Section: Discussionmentioning
confidence: 99%